2020
DOI: 10.1080/13102818.2020.1856717
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an enclosed air-lift photobioreactor (ALPBR) for biomass and lipid biosynthesis of microalgal cells grown under fluid-induced shear stress

Abstract: An enclosed air-lift photobioreactor (ALPBR) is considered an efficient lab-scale bioreactor for microalgae cell growth and lipid biosynthesis. However, fluid-induced shear stress and mixing are two main factors that affect physiological metabolism in microalgal cell cultures. Herein, a 50-L ALPBR after being designed and manufactured was evaluated for microalgal suspension culture. Moreover, computational fluid dynamics (CFD) simulation was used to characterize the hydrodynamics of ALPBR. Specifically, two mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…Moreover, increasing in the gas velocity improved a better mixing in bioreactor so that microalgae could move faster toward the light, which caused a better light absorption hence, the microalgae had a better photosynthesis and growth rate. In a similar study (Ding et al 2021) which carried out in a 50 L airlift photobioreactor with 38 L working volume and 5.0% input CO2, at air flow rates of 8.0, 12.0 the maximum dry cell of Chlorella protothecoides was achieved 0.24 g/L at 12.0 L/min and 300 h. They found that when the aeration rate was 8.0 L/min, the final biomass concentration of C. protothecoides reached 0.32 g/L at 500h, in contrast, in the aeration rate of 12.0 L/min for 300 h the dry weight was 0.24 g/L, which was higher than at 8.0 L/min and 300 h. Also, it was observed that the maximum biomass concentration of Spirulina platensis in the batch cultivation and continuously preharvesting (different operation mode) was 3.383 and 4.893 g L -1 after 11 days' cultivation respectively (Liu et al 2018). whereas this experiment carried out (5% CO2 in air) and 100 mL min -1 gas flow rate in one hollow cylinder with total working volume 1L and in Zarrounk culture medium.…”
Section: Growth Measurement Analysismentioning
confidence: 79%
See 1 more Smart Citation
“…Moreover, increasing in the gas velocity improved a better mixing in bioreactor so that microalgae could move faster toward the light, which caused a better light absorption hence, the microalgae had a better photosynthesis and growth rate. In a similar study (Ding et al 2021) which carried out in a 50 L airlift photobioreactor with 38 L working volume and 5.0% input CO2, at air flow rates of 8.0, 12.0 the maximum dry cell of Chlorella protothecoides was achieved 0.24 g/L at 12.0 L/min and 300 h. They found that when the aeration rate was 8.0 L/min, the final biomass concentration of C. protothecoides reached 0.32 g/L at 500h, in contrast, in the aeration rate of 12.0 L/min for 300 h the dry weight was 0.24 g/L, which was higher than at 8.0 L/min and 300 h. Also, it was observed that the maximum biomass concentration of Spirulina platensis in the batch cultivation and continuously preharvesting (different operation mode) was 3.383 and 4.893 g L -1 after 11 days' cultivation respectively (Liu et al 2018). whereas this experiment carried out (5% CO2 in air) and 100 mL min -1 gas flow rate in one hollow cylinder with total working volume 1L and in Zarrounk culture medium.…”
Section: Growth Measurement Analysismentioning
confidence: 79%
“…Besides, gas holdup is affected by superficial gas velocity, which is called gas flow. By increase gas flow into the reactor, gas holdups in riser and downcomer increase as a result, liquid circulation velocity rise and bubbles which move smoothly in the downcomer and riser and they have spherical shape, despite keeping their shape, larger bubbles move faster and descend to the downcomer which lead to the better light accessibility to microalgae (Ding et al 2021, Rengel et al 2012. However, in higher air flow rates, as liquid circulation velocity increases microalgae cannot stay a long time in downcomer so that they are not able to utilize light efficiently (Sánchez Mirón et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…They confirmed that total gas holdup increases linearly with the inlet gas velocity in the range of velocity investigated. The reason for this was the change in the shape and nature of gas bubbles at a higher velocity of the inlet gas [30,47,48]. As gas velocity increased, bubble size also increased (larger bubbles were released from the sparger at the bottom), but as these large bubbles rose in the liquid column, they quickly broke down into small bubbles; as a result, the number of smaller bubbles increased and the mean bubble diameter decreased, which is presented in Table 4; also the accumulation of large bubbles in the center and small ones along the walls of the reactor was observed.…”
Section: Gas Holdup and Bubble Behavior In Distilled Watermentioning
confidence: 99%
“…As the gas flow rate increases, the gas holdup in the riser and downcomer increases, and as a result, the liquid circulation and bubble velocities increase. Larger bubbles move faster and descend to the downcomer, which results in better light absorption by cyanobacteria [29,30]. However, as the liquid velocity increases at higher gas flow rates, cyanobacteria do not remain in the downcomer long enough to utilize light efficiently [31] and may suffer from shear stress.…”
Section: Introductionmentioning
confidence: 99%
“…Vertical-column/airlift photobioreactors Vertical-column/airlift PBRs are low in cost, available in various designs and scales, and have been tested for the easy cultivation of monoalgal cultures under controlled and aseptic conditions. [49][50][51][52][53][54] Vertical tubular PBRs consist of a cylinder made of transparent glass or PVC with a sparger located usually at the bottom and external or internal illumination. This typical reactor is called a bubble column reactor.…”
Section: Tubular Photobioreactorsmentioning
confidence: 99%